Problems of National Integration in Pakistan - Gulshan Majeed (Journal of Political Studies, 2014)
The problem of national integration has a direct bearing on national unity. Almost, all the developing nations of Asia and Africa are facing this twin problem of national integration and national identity. Pakistan is also no exception in this regard. Presence of opprobrious ethnic schism in these plural societies is a major obstacle in the way of growth of a nation. Social cleavages are very dominant feature of politics of these states. The various factors causing inconsistencies and dissensions may be related to major social changes which are taking place in different developing countries. National integration is a quest for wholeness and unity within the geographical form of the country. Many of the new states of Asia and Africa as Rupert Emerson has pointed out " are not yet nations in being but only nations in hope". Common language and culture are considered key elements, which gave birth to the concept of nation state in European countries. The feelings of nationalism in Asian and African countries developed on the basis of different variables not on the basis of just common language and culture. The immediate task faced by the leaders of post independent states of Asia and Africa is to transform primordial sentiments into civil sentiments, to create a national identity out of diverse regional linguistic and cultural identities. This paper explains the concept of national integration and focuses on various problems which Pakistan has been facing since its inception in the way of national integration and to highlight various techniques to resolve the issues of national integration.